West African Palaeolithic history: New archaeological and chronostratigraphic data from the Falémé valley, eastern Senegal. (15th July 2016) - Chevrier, B.; Rasse, M.; Lespez, L.; Tribolo, C.; Hajdas, I.; Guardiola Fígols, M.; Lebrun, B.; Leplongeon, A.; Camara, A.; Huysecom, É.
Abstract: For more than a century, Senegal has yielded abundant Palaeolithic finds, in particular on the Atlantic coast as well as in the Falémé Valley, but the lack of reliable and integrated chrono-cultural data has limited the possibilities of interpretation. These gaps were one of the main factors leading to the launch of a new research programme in the Falémé Valley (eastern Senegal). Its objective since 2012 has been to establish a new archaeological reference sequence in West Africa complementary to that of Ounjougou (Mali). Its more southerly location gave us the opportunity to obtain data to address the issue of human settlement and mobility in relation to changes in aridity and the position of the South-Saharan limit, along the north-south axis of the Falémé Valley. Field survey enabled the identification of a very large number of sites, some in primary context, thus confirming the potential of the region. Geomorphological analysis and initial chronological results indicate relatively continuous and fairly complex deposition, with the alternation of fine-grained and coarser deposits, in particular for Marine Isotope Stages (MIS) 3 and 2. From an archaeological viewpoint, while artefacts attributed to very early periods (prior to isotope stages 4/5) were found in reworked contexts, several MIS 2, or even MIS 3 occupations up to the early Holocene (Ravin des Guêpiers, Fatandi, Toumboura, Missira), attracted significant attention. These sites provide complete, precise and reliable information. They contain assemblages using different techniques of production, which raise questions regarding cultural rhythms and changes, and show evidence of populations present during the hyperarid "Ogolian", during which the Ounjougou sequence has a major sedimentary and archaeological hiatus for this period.